Components of Educational Psychology in Islamic Perspective and Its Implications for Learning: A Literature Review - Nurrahma Nurrahma; Lukman Gappar; Supriandi Supriandi (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to analyze the components of educational psychology from an Islamic perspective through a library research approach. The study was conducted by examining classical and modern literature on Islamic psychology, Western theories of educational psychology, as well as the works of scholars such as Al-Ghazali, Ibn Sina, and Ibn Khaldun. Data analysis uses content analysis techniques which include theme identification, categorization of educational psychology components, synthesis of Western and Islamic concepts, and formulation of learning implications. The results of the study show that educational psychology in Islam has a more holistic approach because it includes cognitive, affective, motivational, interest, individual development, social interaction, and spiritual dimensions. The Islamic perspective emphasizes the integration of the values of tauhid, adab, intention, and tazkiyatun nafs in the entire educational process. The integration of modern theory and Islamic values has been proven to increase intrinsic motivation, critical thinking skills, interest in learning, character formation, and balance of students' development. This research confirms that Islamic-based educational psychology is a comprehensive and relevant paradigm to face contemporary educational challenges. This approach has the potential to produce students who are intellectually superior, have noble character, and have spiritual depth, so that it is in line with the goal of Islamic education to form kamil people.